1994
DOI: 10.1002/ceat.270170306
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of ethanol over zeolite H‐ZSM‐5

Abstract: The conversion of ethanol over H-ZSM-5 was studied as a function of ethanol partial pressure, reaction temperature, weight hourly space velocity and %/A1 ratio. The results obtained were in qualitative agreement with most of those in the literature. Combination with all published results to give a significant regression model was not possible due to the large scatter of the data from various scientific groups. In mechanistic investigations, temperature programmed reaction measurements of ethanol, diethyl ether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
91
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 39 publications
15
91
0
2
Order By: Relevance
“…Accordingly, the HZSM-5 zeolite is effective below 300 C and has been used with different modifications aimed at moderating its acid strength to avoid secondary reactions of ethylene conversion and to attenuate coke formation. [16][17][18][19][20] However, propylene and butene production takes place by transformation of ethylene through a oligomerization-cracking mechanism that requires temperatures above 350 C. [21][22][23] The main difficulty of this process is catalyst deactivation, although a distinction must be made between reversible deactivation (due to coke deposition) and the zeolite irreversible deactivation due to water content in the reaction medium (dealuminization). 24 In a previous study, the good performance of a catalyst based on a HZSM-5 zeolite treated with 0.2 M NaOH solution for 10 min has been proven.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the HZSM-5 zeolite is effective below 300 C and has been used with different modifications aimed at moderating its acid strength to avoid secondary reactions of ethylene conversion and to attenuate coke formation. [16][17][18][19][20] However, propylene and butene production takes place by transformation of ethylene through a oligomerization-cracking mechanism that requires temperatures above 350 C. [21][22][23] The main difficulty of this process is catalyst deactivation, although a distinction must be made between reversible deactivation (due to coke deposition) and the zeolite irreversible deactivation due to water content in the reaction medium (dealuminization). 24 In a previous study, the good performance of a catalyst based on a HZSM-5 zeolite treated with 0.2 M NaOH solution for 10 min has been proven.…”
Section: Introductionmentioning
confidence: 99%
“…03, pp. 503 -513, July -September, 2016 pylene yield as suggested by Schulz and Bandermann (1994), Inaba et al (2006), Song et al (2010) and Duan et al (2012).…”
Section: Methodsmentioning
confidence: 93%
“…After 228 minutes, for ethanol partial pressure values above 0.2 atm, the propylene yield stabilized around 12%. Schulz and Bandermann (1994) studied the effects of ethanol partial pressure on the product distribution over HZSM-5 and found that an increase in ethanol partial pressure decreased the yield of olefins while increasing that of aromatic compounds. Similar results can be observed in Figure 8(b).…”
Section: Catalytic Testsmentioning
confidence: 99%
“…Previous studies reported that HZSM-5 zeolite with strong Brønsted acid sites was an effective catalyst for this transformation [22]. However, deactivation due to coke formation on its surface led to decreasing activity and selectivity towards ethylene [23] and therefore made the process unsuitable for industrial applications [24]. Phillips and Datta [25] investigated the production of ethylene from hydrous ethanol over HZSM-5 under mild conditions and demonstrated that strong Brønsted acid sites led to rapid catalyst deactivation in the initial stages through the oligomerization of ethylene and the formation of carbonaceous species.…”
Section: Introductionmentioning
confidence: 99%